1986
DOI: 10.1016/s0022-5347(17)46074-5
|View full text |Cite
|
Sign up to set email alerts
|

A New Mouse Model of Genetically Transmitted Polycystic Kidney Disease

Abstract: The clinical and pathologic characteristics of the murine polycystic kidney were examined in a mutant cy/cy mouse found in the KK strain, which is known to be a diabetic strain. This cy/cy mutant appeared to resemble human adult polycystic kidney disease in clinical course and morphology although inheritance was an autosomal recessive trait. Histologic studies of early postnatal animals suggested that cystic alterations might occur in any part of a collecting tubule or nephron. The cy/cy mutant might be a usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…In this anormaly, the number of visible cysts on the kidney surface increases with age In mice, there are a few mutants having shorted long bones and bent thoracic vertebral column due to cartilage anormaly [4] or musculoskeletal abnormalities [3]. Congenital polycystic kidneys in mice have been reported by Russell [6] and others [2,10]. Dunn [1] reported that the ur/ur mice had urogenital abnormalities associated with other congenital malformations.…”
Section: Discussionmentioning
confidence: 99%
“…In this anormaly, the number of visible cysts on the kidney surface increases with age In mice, there are a few mutants having shorted long bones and bent thoracic vertebral column due to cartilage anormaly [4] or musculoskeletal abnormalities [3]. Congenital polycystic kidneys in mice have been reported by Russell [6] and others [2,10]. Dunn [1] reported that the ur/ur mice had urogenital abnormalities associated with other congenital malformations.…”
Section: Discussionmentioning
confidence: 99%
“…The adult type is an autosomal dominant polycystic kidney disease (ADPKD) and the infant type is an autosomal recessive polycystic kidney disease (ARPKD). Although many spontaneously occurring polycystic kidney mouse models have been established [1,3,4,8,10,12,13], the Cy rat [2,5,6,11] and the chin rat [9] are the only rat models. At Charles River Japan Inc., we have identified a female rat with polycysts on both the kidney and liver derived from an ongoing colony of Crj:CD (SD) rats.…”
mentioning
confidence: 99%
“…This disease progressed slowly in the KK strain resulting in death at approximately six months of age [9]. In the late stages both anemia and azotemia were observed [8,9,10] . This abnormality was shown to be genetically controlled by an autosomal recessive mutation [8,9].…”
mentioning
confidence: 99%